RESILIENSI MASYARAKAT PADA ASPEK SOSIAL, TERHADAP BENCANA BANJIR DI DESA LABANSARI, KECAMATAN CIKARANG TIMUR, KABUPATEN BEKASI - Fachry Arsyad (Politeknik Kesejahteraan Sosial Bandung, 2022)
Bekasi Regency, there are several areas that often experience floods, one of which is Labansari Village, East Cikarang. This village is a flood-prone area, due to its geographical factors, where this area is a confluence of 2 rivers, namely the Cibeet and Citarum Rivers. In this regard, it is necessary to reduce disaster risk through increased resilience. In order to increase resilience, resilience assessment is an important step, because through a resilience assessment, the results can determine whether a community is deemed capable of absorbing shocks, repairing damage and adapting to disasters. Resilience assessment is carried out using the concept of CDRI (Climate & Disaster Resilience Initiative). CDRI is used, because it is in accordance with the conditions of the selected research location. In addition, the resilience that is measured focuses on social aspects, because resilience to natural disasters is obtained from relationships or connections between people, and has links with the field of social work. This study aims to: (1) Assess the resilience of social aspects to floods using the CDRI concept and (2) Explain the role of social workers to increase regional resilience to floods according to social aspects. Quantitative descriptive method was used in this study, with data collection using a survey method. The results of the social aspect resilience assessment show that Labansari Village has high resilience with a value of 3.59. As for some of the variables in it, it is necessary to improve, where the role of social workers can be applied to support the increase in several resilience variables.Abstract is written concisely and factually, includes the purpose of research, the method of research, the result and conclusion of research. Abstract is written in English and Indonesian language, in account between 150 – 250 words in one paragraph, font Times New Roman 12.